Research note: Investigating correlations of poultry SCFAs in duodenum, cecum, liver and serum with cecum microbiota and residual feed intake - Zhengxiao He; Alan G Fahey; Ranran Liu; Jie Wen; Guiping Zhao (Poultry Science, 2025)
Background: Short-chain fatty acids (SCFAs) are essential metabolites which play an important role in biological functions such as energy homeostasis and immune function. However, duodenum, liver and serum have different biological functions, and SCFAs were also detected in these sites. This study aims to compare the SCFA composition of the liver, serum, and duodenum and estimate the correlation between SCFAs and residual feed intake (RFI) in broilers. Method: Broiler chickens from a commercial breeding paternal line were used in this study. The liver, serum, duodenum and cecum SCFA concentrations were detected through the LC-MS method. Cecum microbe was sequenced through the V4 region and annotated by the SLIVA_123 database. The co-occurrence networks were based on the Spearman correlations, and the bi-direction two-sample Mendelian randomisation method (TMR) was used to investigate the causal effect between SCFAs and RFI. Result: Liver, duodenum, and serum content had similar SCFA compositions. Compared to the other three sites, the cecum contains a variety of microbiota, as the different SCFAs are produced by microbiota. The causal investigation between SCFA with RFI were first investigated in this study. The bidirectional Mendelian randomisation results illustrated that RFI could have a causal effect on four cecum SCFAs. In contrast, there is no causal effect of cecum SCFAs on RFI disagreed with many nutritional trials, and the contradiction needs further investigation.